Financial crisis, contagion, and containment : from Asia to Argentina - Desai, Padma (Princeton University Press, 2003)
This book provides a sweeping, up-to-date, and boldly critical account of the financial crises that rocked East Asia and other parts of the world beginning with the collapse of the Thai baht in 1997. Retracing the story of Asia's ""Crisis Five""--Indonesia, Malaysia, South Korea, the Philippines, and Thailand--Padma Desai argues that the region's imprudently fast-paced opening to the free flow of capital was pushed by determined advocates, official and private, in the global economy's U.S.-led developed center. Turmoil ensued in these peripheral economies, the Russian ruble faltered, and Braz